Development and validation of a prognostic model incorporating tumor thrombus grading for nonmetastatic clear cell renal cell carcinoma with tumor thrombus: A multicohort study - Le Qu; Hui Chen; Qi Chen; Silun Ge; Aimin Jiang; Nengwang Yu; Yulin Zhou; Michał Kunc; Ye Zhou; Xiang Feng; Wei Zhai; Zhenjie Wu; et al. (MedComm, 2023)
Abstract There is significant variability with respect to the prognosis of nonmetastatic clear cell renal cell carcinoma (ccRCC) patients with venous tumor thrombus (VTT). By applying multiregion whole‐exome sequencing on normal‐tumor‐thrombus‐metastasis quadruples from 33 ccRCC patients, we showed that metastases were mainly seeded by VTT (81.8%) rather than primary tumors (PTs). A total of 706 nonmetastatic ccRCC patients with VTT from three independent cohorts were included in this study. C‐index analysis revealed that pathological grading of VTT outperformed other indicators in risk assessment (OS: 0.663 versus 0.501–0.610, 0.667 versus 0.544–0.651, and 0.719 versus 0.511–0.700 for Training, China‐Validation, and Poland‐Validation cohorts, respectively). We constructed a risk predicting model, TT‐GPS score, based on four independent variables: VTT height, VTT grading, perinephric fat invasion, and sarcomatoid differentiation in PT. The TT‐GPS score displayed better discriminatory ability (OS, c‐index: 0.706–0.840, AUC: 0.788–0.874; DFS, c‐index: 0.691–0.717, AUC: 0.771–0.789) than previously reported models in risk assessment. In conclusion, we identified for the first‐time pathological grading of VTT as an unheeded prognostic factor. By incorporating VTT grading, the TT‐GPS score is a promising prognostic tool in predicting the survival of nonmetastatic ccRCC patients with VTT.